The Effect of The Use of Educational Toys Made of Nature on Fine Motor Development in Early Childhood - Nuri, Nuri Aldhila Maqother; Sukardi, Sukardi; Ika Rachmayani , Ika Rachmayani; Baik Nilawati Astini, Baik Nilawati Astini (UIN Mataram, 2024)
The study aims to determine whether or not the use of natural educational games has an impact on fine motor development in early childhood. This research uses a quantitative approach with quasi-experimental experimental methods. This study was carried out in RA Perwanida 2 Mataram on children of group B. From the results that have been done educational play tools have been shown to be able to improve fine motorics of early childhood who previously motoric fine children are not very active in their daily life and this can be seen in the experimental group. This is because educational play tools in children's learning activities are very suitable for stimulating the child's natural motor potential which can be obtained from the surrounding environment.